LAND GOVERNANCE AND THE UNFULFILLED PROMISE OF ACEH’S SPECIAL AUTONOMY: LEGAL SCHISM AND POLITICAL STRESS - Helfianti, Sutri; Jalil, Husni; Adwani; Azhari (Veredas do Direito, 2025)
Aceh province is designated as a region with special status, as outlined in the Indonesian Law No. 11 of 2006 on the Governance of Aceh. A distinguishing feature of Aceh is its autonomous jurisdiction over land rights administration, necessitating the establishment of an Aceh Land Agency by the government. Nonetheless, in practice, this authority remains governed by the National Land Agency. This article seeks to analyse the central government's dedication to transferring central power over land issues to the Aceh government. This study utilises a normative legal research methodology, with primary data sourced from legislation and interviews with pertinent stakeholders. Secondary data is derived from relevant journals for this study. The study's findings reveal that the central government has failed to enforce Law No. 11 of 2006, which requires the creation of a Land Agency in Aceh, as outlined in Article 253(1) of the Aceh Government Law. The lack of commitment from the central government has created ambiguity in land management in Aceh, resulting in a loss of legal clarity necessary for effective land administration among the public. The restricted jurisdiction of the Aceh Land Office, coupled with ongoing supervision of land issues by the Regional Office of the National Land Agency, has impeded the realisation of the advantages of land autonomy as mandated by law.